Challenges for increasing the sustainability of engineering faculties: a case study in Indonesian private university - Talar, Yulianti; Gozaly, Jimmy (Intelektual Pustaka Media Utama, 2025)
In Indonesia, the percentage of students dropping out from private universities is always much higher than that of public universities, and the second-highest number of dropouts comes from the engineering field. This study aims to improve the sustainability of engineering faculty in Indonesian private universities by obtaining variables that affect engineering student retention and finding the pattern for each category of student retention. Data was gathered through a questionnaire from 297 engineering faculty students. The questionnaire consists of 34 independent variables using academic performance, attitudes and satisfaction, academic engagement, social and family support, and four categories of student retention (persister, stop-out, slow-down, leaver) as dependent variables. According to discriminant analysis, grade point average (GPA) and student satisfaction in social relationships with fellow students influence engineering student retention. To increase engineering student retention, increasing student satisfaction in social relations with fellow students needs to be prioritized over GPA because the leaver and stop-out categories have a similar pattern, namely high GPA but low satisfaction with social relations with fellow students. Through this research, several efforts are proposed that need to be made by institutions to improve engineering student retention and the sustainability of engineering faculty in Indonesia.